Toward Low‐Level Turbulence Forecasting at Eddy‐Resolving Scales - Domingo Muñoz‐Esparza; Robert Sharman; Jeremy Sauer; Branko Kosović (Geophysical Research Letters)
Abstract Microscale turbulence in the atmospheric boundary layer (ABL) is characterized by significant spatiotemporal variability. Consequently, a change in the turbulence forecasting paradigm needs to occur, moving beyond average turbulence estimates at mesoscale grid resolutions (several kilometers) to eddy‐resolving forecasts. To that end, the viability of dynamic downscaling to large‐eddy simulation scales is evaluated. We present for the first time, multiday dynamic downscaling from currently available numerical weather prediction forecasts to a high‐resolution grid spacing of 25 m. It is found that these eddy‐resolving forecasts can realistically reproduce turbulence levels and peak events in the bulk of the daytime ABL, adequately capturing turbulence variability at subminute intervals. Moreover, probability distributions of turbulence quantities are in very good agreement when compared to in situ sonic‐anemometer observations. These results demonstrate the feasibility of eddy‐resolving forecasts to derive accurate probabilistic estimates of turbulence in the ABL and provide a path toward real‐time large‐eddy simulation scale prediction.